Mammary‐type myofibroblastoma of the perineum: Typical or rare location?. Issue 3 (23rd February 2022) - Naito, Akihiro; Takeshima, Yuta; Takahashi, Sayuri
Abstract : Introduction: Mammary‐type myofibroblastoma is a rare benign tumor, mainly arising along the embryonal mammary ridge. We report a rare case of mammary‐type myofibroblastoma of the perineum. Case presentation: A 37‐year‐old Japanese man presented with a 20 mm, progressively‐growing painless mass in the right perineum. Computed tomography showed a subcutaneous tumor with a strong contrast effect. Upon total resection, pathology showed a spindle‐cell tumor positive for desmin but negative for CD34. Further immunohistochemistry showed loss of Rb expression, leading to differential diagnosis. We could not evaluate the exact rarity of the perineal location due to categorization in past reports. Conclusion: Due to the similarities between mammary and anogenital tissue, we suggest that tallying perineal and vulvar areas separately from the embryonic mammary ridge sites may be beneficial in gaining insight into the pathophysiology of this tumor.